2012
DOI: 10.1016/j.eurpsy.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of overweight/obesity on cognitive function in euthymic individuals with bipolar disorder

Abstract: BackgroundPersistent impairment in cognitive function has been described in euthymic individuals with bipolar disorder. Collective work indicates that obesity is associated with reduced cognitive function in otherwise healthy individuals. This sub-group post-hoc analysis preliminarily explores and examines the association between overweight/obesity and cognitive function in euthymic individuals with bipolar disorder.MethodsEuthymic adults with DSM-IV-TR-defined bipolar I or II disorder were enrolled. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 42 publications
6
57
0
Order By: Relevance
“…Long-term use of high fat diet or high energy diet could induce obesity and affect serum lipid levels and oxidative stress, which in turn affect learning and memory functions [37,38,39]. The traditional Mediterranean-style diet has fewer meats and carbohydrates and more plant-based foods and monounsaturated fat than a typical American diet.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of high fat diet or high energy diet could induce obesity and affect serum lipid levels and oxidative stress, which in turn affect learning and memory functions [37,38,39]. The traditional Mediterranean-style diet has fewer meats and carbohydrates and more plant-based foods and monounsaturated fat than a typical American diet.…”
Section: Discussionmentioning
confidence: 99%
“…Over-weight ⁄ obesity has also been shown to have a negative impact on long-term treatment response (283,289) and on cognitive function in euthymic patients with BD (292).…”
Section: Prevalence and Impactmentioning
confidence: 99%
“…However, to date, only one study has shown that overweight patients with BD performed poorly on tasks assessing processing speed and attention when compared with normal weight patients with BD. 13 Participants in our study had an average duration of illness of 15 years and a mean of 7 episodes of both depression and mania, which indicates that obesity may negatively impact cognition in patients with established illness. However, the impact of overweight and obesity on cognitive functioning in patients early in the course of BD is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To date, such predictors include medications, namely, mood stabilizers and atypical antipsychotics, 1,[6][7][8][9] substance abuse or dependence, 10 duration of illness and number of episodes, 1,6,11 childhood trauma, 12 and possibly obesity. 13 The deficits in the broad domains of attention, learning-memory, and executive function are also present even in patients with first-episode mania, where the variables associated with the progression of BD are fewer. [14][15][16] Overweight and (or) obesity have been reported to have a significant impact on the clinical course of BD, and potentially on cognitive functioning.…”
Section: Limitationsmentioning
confidence: 99%